Expectations of Prison Execution and Protection Officers Orientation Their Children to Sports - Kutlu, Cahit; Savucu, Yüksel (İbrahim ERDEMİR, 2024)
Aim: It is seen that factors such as family, social environment and friends are effective in the child's orientation to sports. In our study, it was aimed to determine the expectations of prison and protection officers who orientation their children to sports in Elazığ. For this purpose, it was tried to emphasize the importance of raising the awareness of families and the creation of a healthy life profile. Method: The research was carried out in 11 Penitentiary Institutions in Elazığ. While approximately 1000 prison guards consist of our universe, total 486 prison guards were included in the sample group. “The Expectations of Parents Who Orientation Their Children to Sports” questionnaire (Survey) was applied in this study. The survey consists of two parts. The first part is about the demographic features of the subjects (such as age, gender, educational status), and the second part is aimed at defining the expectations of the prison and protection officers in their children's orientation to sports. Results: SPSS 22 program was used in the analysis of the data. The significance levels of statistical analyzes were determined according to p

Amaç: Çocuğun spora yönelmesinde aile, sosyal çevre, arkadaş gibi ögelerin etkili olduğu görülmektedir. Çalışmamızda Elâzığ ilinde görev yapan çocuklarını spora yönlendiren ceza infaz ve koruma memurlarının beklentilerinin belirlenmesi amaçlanmıştır. Bu amaç doğrultusunda ailelerin bilinçlendirilmesi ve sporun sağlıklı bir yaşam profili oluşturulmasındaki önemi vurgulanmaya çalışılmıştır. Gereç ve Yöntem: Araştırma, Elâzığ ilinde toplam 11 ceza infaz kurumunda gerçekleştirilmiştir. Evrenimizi yaklaşık 1000 ceza ve infaz memuru oluştururken, toplam 486 ceza ve infaz memuru örneklem grubuna dâhil edilmiştir. Bu araştırmada; betimsel tarama (Survey) modeli “Çocuklarını Spora Yönlendiren Anne ve Babaların Beklentileri” anketi uygulanmıştır. Anket iki bölümden oluşmaktadır. Birinci bölüm deneklerin demografik özellikleri (yaş, cinsiyet, eğitim durumu gibi), ikinci bölüm ise ceza infaz ve koruma memurlarının çocuklarının spora yönelmesindeki beklentilerini tanımlamaya yöneliktir. Bulgular: Araştırmada istatistiksel analizlerin anlamlılık düzeyleri p
Çocuklarını Spora Yönlendiren Ceza İnfaz ve Koruma Memurlarının Beklentilerinin Belirlenmesi
Keywords: Physical Training and Sports; Beden Eğitimi ve Oyun